Cost and Profit Efficiencies of Fully-Fledged Islamic Banks and Islamic Windows of Conventional Banks in Pakistan - Qureshi, Asfandyar Hasan (2013)
Pakistan is an emerging and an important country in banking and finance. A lot of emphasis has been made on the Islamic banking sector of Pakistan and its growth in the past decade is plausible. It is opening up the market for international investors. This makes the Islamic banking sector of Pakistan interesting and worth analysing. Furthermore, it has not been taken up widely in the academic literature. The purpose of this research is to present a new perspective on the evaluation of x-efficiencies in Pakistani Islamic banking system. As per the knowledge of the author this is the first time such a study has been conducted for Pakistani banks where a comparison has been made between the cost and profit efficiencies of fully-fledged Islamic banks and the Islamic banking windows of the conventional Banks.